Protection of personal Data in the Era of Artificial Intelligence - HARKATI, Djamila (Journal of Human Sciences, 2025)
This research paper highlights the challenges faced by legal frameworks in protecting personal data in the context of artificial intelligence. The study examines the most significant risks to data owners, acknowledging that it is nearly impossible to enumerate all potential harms due to the continuous technological advancements in AI systems. Additionally, we explore the key mechanisms established by legislators to mitigate these risks, focusing on both legislative protection and the available technical safeguards for personal data. However, these measures require further adjustments to keep pace with rapid technological developments, particularly given the widespread adoption of artificial intelligence.